Factors Associated with Long-term Weight Loss Maintenance Following Bariatric Surgery in Adolescents with Severe Obesity - Ryder, Justin R. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Bariatric surgery produces robust weight-loss, however, factors associated with long-term weight-loss maintenance among adolescents undergoing Roux-en-Y gastric bypass surgery (RYGB) are unknown. SUBJECTS/METHODS: Fifty adolescents (mean±SD age and BMI = 17.1±1.7yrs and 59±11kg/m(2)) underwent RYGB, had follow-up visits at 1-yr and at a visit between 5–12yrs following surgery (FABS-5+ visit; mean±SD 8.1±1.6yrs). A non-surgical comparison group (n=30; mean±SD age and BMI = 15.3±1.7yrs and BMI=52±8kg/m(2)) was recruited to compare weight trajectories over-time. Questionnaires (health-related and eating behaviors, health responsibility, impact of weight on quality of life, international physical activity questionnaire (IPAQ), and dietary habits via surgery guidelines) were administered at the FABS-5+ visit. Post-hoc, participants were split into 2 groups: long-term weight loss maintainers (n=23; baseline BMI=58.2kg/m(2); 1-yr BMI=35.8kg/m(2); FABS-5+ BMI=34.9kg/m(2)) and re-gainers (n=27; baseline BMI=59.8kg/m(2); 1-yr BMI=36.8 kg/m(2); FABS-5+ BMI=48.0kg/m(2)) to compare factors which might contribute to differences. Data were analyzed using generalized estimating equations adjusted for age, sex, baseline BMI, baseline diabetes status, and length of follow-up. RESULTS: The BMI of the surgical group declined from baseline to 1-yr (−38.5±6.9%), which, despite some regain, was largely maintained until FABS-5+ (−29.6±13.9 % change). The BMI of the comparison group increased from baseline to the FABS-5+ visit (+10.3±20.6%). When the surgical group was split into maintainers and re-gainers, no differences in weight-related and eating behaviors, health responsibility, physical activity/inactivity, or dietary habits were observed between groups. However, at FABS-5+, maintainers had greater overall QOL scores than re-gainers (87.5±10.5 vs. 65.4±20.2, p<0.001) and in each QOL sub-domain (p<0.01 all). CONCLUSIONS: Long-term weight outcomes for those who underwent weight loss surgery were superior to those who did not undergo surgical treatment. While no behavioral factors were identified as predictors of success in long-term weight-loss maintenance, greater QOL was strongly associated with maintenance of weight loss among adolescents who underwent RYGB surgery.